PELAKSANAAN PROGRAM BADAN RESTORASI GAMBUT DI DESA RIMBO PANJANG KABUPATEN KAMPAR TAHUN 2017 - Puspita, Liza; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
In repairing peatlands damaged by burning, the President forms a non-structural institution that is directly responsible to the President. For this reason, the President issued Presidential Regulation Number 1 of 2016 concerning the Peat Restoration Agency. The researcher wanted to see the Implementation of the Peat Restoration Agency Program in Kampar District in 2017 (Study of Rimbo Panjang Village).This study aims to describe the Implementation of the Peat Restoration Agency Program in Rimbo Panjang Village, Kampar Regency in 2017. This study used a qualitative approach. Research location in Rimbo Panjang Village. Data sources in this study are informants, documents and print media. Data collection techniques were carried out by interviews and documentation. While the data analysis technique is done by qualitative analysis which is descriptive type, which is trying to analyze using the theory of policy implementation.The conclusion of this study is that the implementation of the Peat Restoration Agency Program in Rimbo Panjang Village, Kampar Regency in 2017 has not been optimally seen from the rewetting program and the economic revitalization of the community. In the implementation of the Peat Restoration Agency program in Rimbo Panjang Village, the program has been carried out by building bore wells. Construction of drill wells is more effective for Rimbo Panjang Village which is located far from natural water sources. However, in the implementation of this program there was a lack of communication between the Peat Restoration Agency, the Rimbo Panjang Village Government and the Community Concerned Fire and the unclear operational funds that made the program not running optimally. In addition, the Peat Restoration Agency is also a community economic revitalization program. However, this program has not been implemented until 2017 in Rimbo Panjang Village.Keywords: Program, Peat Restoration Agency